MODEL PERFORMANCE ASSESSMENT OF LEARNING OUTCOMES OF VOLLEY BALL IN ELEMENTARY SCHOOL (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2012)
AbstrakTujuan penelitian ini adalah untuk menghasilkan: 1) model penilaian kinerja hasil pembelajaranpermainan bola voli di sekolah dasar, 2) mengetahui validitas dan reliabilitas, 3) mengetahuiindikator yang dapat diukur secara terpadu dan kontekstual pada penilaian kinerja hasilpembelajaran permainan bola voli di sekolah dasar. Penelitian ini menggunakan pendekatanpenelitian dan pengembangan. Hasil yang diperoleh adalah 1) model penilaian kinerja hasilpembelajaran permainan bola voli di sekolah dasar, 2) penilaian kinerja hasil pembelajaranpermainan bola voli mempunyai koefisien validitas isi melalui pendekatan content validityratio (CVR) sebesar 1, 3) penilaian kinerja hasil pembelajaran permainan bola voli mempunyaikoefisien reliabilitas inter rater 0,927 dengan varians eror 0,528, koefisien reliabilitas interrater pada indikator kognitif 0,778 dengan varians eror 0,19, koefisien reliabilitas inter raterpada indikator psikomotor 0,809 dengan varians eror 0,272, koefisien reliabilitas inter raterpada indikator afektif 0,798 dengan varians eror 0,207, 3) indikator yang dapat diukur secaraterpadu terdiri dari kognitif, psikomotor dan afektif. AbstractThis research aims to: 1) produce model performance assessment of learning outcomes ofvolley ball in elementary school, 2) examine the coefficient of validity and the reliability, 3) examine the indicators that can be measured in an integrated and contextual performanceon the assessment of learning outcomes of volleyball in elementary school. This research usedthe approach of research and development. The results are: 1) model performance assessmentof learning outcomes of volleyball in elementary school, 2) performance assessment of learningoutcomes of volleyball that has content validity coefficient through content validity ratio(CVR) approach of 1, and performance assessment of learning outcomes of volleyball; theinter-rater reliability coefficient was 0,927 and the varians error was 0,528, coefficient of interraterreliability on cognitive indicator was 0,778 and the varians error was 0,19, inter-raterreliability coefficient on psychomotor indicator was 0,809 and the varians error was 0,272,coefficient of inter-rater reliability on affective indicator was 0,798 and the varians error was0,207, 3) measurable indicators that consist of cognitive, psychomotor, and affective aspects.